Towards carbon monoxide detection based on ZnO nanostructures - Desimone, Paula Mariela; Zonta, Giulia; Giulietti, Giuliana; Ortega, Pedro Paulo [UNESP]; Aldao, Celso Manuel; Simões, Alexandre Zirpoli [UNESP]; Moura, Francisco; Ponce, Miguel Adolfo; Foschini, Cesar Renato [UNESP] (My University, 2024)
In this work, we investigated how the morphology of ZnO nanostructures influenced their CO detection. ZnO nanoparticles and nanorods were synthesized using the MAH method. XRD confirmed the formation of wurtzite ZnO without secondary phases. Raman spectroscopy revealed that oxygen vacancies, zinc interstitial, and their free carriers are the dominant defects. The nanorod morphology enhanced the performance towards CO when compared with the nanoparticles. The ZnO nanorods have a higher specific surface area and are more sensitive to CO. The CO detection performance of the ZnO nanorods highlights how the CTAB employed in the synthesis changed the structural defects or states localized inside the bandgap. Moreover, the use of the MAH method with CTAB is important due to the short treatment time, low temperature, and the possibility to control the morphologies of the ZnO nanostructures. Also, the ZnO nanorods response to CO shows their potential as a gas-sensing component.
Keywords: Carbon monoxide; Conductivity; Semiconductor gas sensors; ZnO morphologies